VISUAL EXPRESSION OF THE LOTUS FLOWER PHILOSOPHY IN PAINTING ARTWORKS - Prayoga, I Made; Budiaprilliana, Luh; Budiarta, I Dewa Putu Gede (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This report explains the creation of a painting with the theme "Visual Expression of Lotus Flower Philosophy in Painting". The abstract of the lotus flower philosophy describes the beauty that emerges from less than ideal conditions, where the lotus grows from mud but remains clean and beautiful on the surface of the water. In its life, the lotus flower is a plant with beautiful flowers, but behind the beauty of its flowers, the plant grows in a muddy and dirty environment to achieve the beauty of the lotus flower. This abstract reviews the application of the lotus flower philosophy in human life, describing how values such as resilience, beauty, and growth can be applied in the context of personal and professional development. The statement about the life of the lotus flower contains important values that can be applied in human life, how values such as resilience, beauty, and growth can be applied in the context of personal and professional development. This philosophy also describes the importance of living in the midst of difficulties, seeking light in the darkness, remaining calm in chaos, and how we process ourselves in finding our identity. By exploring the balance between hardness and softness, and the ability to thrive in difficult environments, this philosophy inspires humans to reach their highest potential in everyday life.This report explains the concept of painting inspired by the philosophy of the lotus flower that can be applied in human life by exploring the aesthetic elements and symbolism in the lotus flower. This painting tries to capture the beauty and meaning of the philosophy of the lotus flower with a creative context. by combining various techniques in one painting that can symbolize the meaning and philosophy of the lotus flower.